2000
DOI: 10.1590/s1516-44462000000200003
|View full text |Cite
|
Sign up to set email alerts
|

Anormalidades de fluxo sangüíneo cerebral em indivíduos dependentes de cocaína

Abstract: INTRODUÇÃO: Nos últimos anos, tem havido relatos de anormalidades do fluxo sanguíneo cerebral em indivíduos com o abuso de cocaína, detectadas por meio de tomografia computadorizada por emissão de fóton único (SPECT). Esse padrão anormal de perfusão cerebral tem sido associado a prejuízos cognitivos mas não a alterações observáveis por meio de exames de neuroimagem estrutural. Um problema envolvendo a maioria dos trabalhos publicados sobre esse tema é a inclusão de um grande número de usuários de heroína nas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…In long-term inhalant dependents of toluene, acetone, benzene and derivatives Kücük et al noted in BSI marked hypoperfusion in the temporal and parietooccipital regions 19 . In contrast, Volkow et al, noted prefrontal cortex hypoperfusion in chronic dependents of inhalants in BSI which correlated with the severity of the apathy that these patients present Tc-ECD and also observed, in isolated patients, perfusion irregularities in the pre-frontal cortex 22 . Hypoperfusion defects in cocaine dependents are caused by vascular occlusion secondary to platelet activation and formation of microthrombi.…”
Section: Discussionmentioning
confidence: 83%
“…In long-term inhalant dependents of toluene, acetone, benzene and derivatives Kücük et al noted in BSI marked hypoperfusion in the temporal and parietooccipital regions 19 . In contrast, Volkow et al, noted prefrontal cortex hypoperfusion in chronic dependents of inhalants in BSI which correlated with the severity of the apathy that these patients present Tc-ECD and also observed, in isolated patients, perfusion irregularities in the pre-frontal cortex 22 . Hypoperfusion defects in cocaine dependents are caused by vascular occlusion secondary to platelet activation and formation of microthrombi.…”
Section: Discussionmentioning
confidence: 83%
“…Entretanto, esse mesmo padrão de alterações de fluxo sangüíneo cerebral foi também descrito num estudo realizado em nosso meio, onde o consumo de drogas opióides é relativamente baixo. 17 Ainda não está claro se essas anormalidades de fluxo são reversíveis ou não. Um trabalho foi capaz de evidenciar anormalidades de perfusão cerebral mesmo após períodos de até seis meses sem consumo de drogas, 18 enquanto outros estudos demonstraram melhora do padrão de fluxo com tratamentos que envolveram buprenorfina (um agonista parcial opióide), 19 ou drogas com atuação sobre a atividade plaquetária.…”
Section: Cocaínaunclassified
“…Our research group has shown that cocaine-use is associated with hypoperfusion in several areas of the brain (3) and that CDI present several cognitive impairments which have real-life implications (1618). We have recently evaluated 30 CDI, after 2 weeks of abstinence, and compared with 32 healthy individuals in frontal executive tasks.…”
Section: Introductionmentioning
confidence: 99%